Estrategias de enseñanza-aprendizaje y su influencia en el déficit de atención de los estudiantes de primer de bachillerato paralelo A de informática en la Unidad Educativa Eugenio Espejo, durante el periodo lectivo 2021 -2022 - Cujilan Meza, Victoria Narcisa (2022)
The research project called, “TEACHING-LEARNING STRATEGIES AND ITS INFLUENCE ON THE ATTENTION DEFICIT OF FIRST HIGH SCHOOL STUDENTS PARALLEL TO COMPUTER SCIENCE IN THE EUGENIO ESPEJO EDUCATIONAL UNIT. DURING THE SCHOOL PERIOD 2021 -2022 ", aims to study the attention deficit that is a very important problem in education, and also the strategies that can be applied with the attention deficit, for this investigation a survey was carried out that through Quantitative research allows obtaining measurable figures, which showed as results that in the unit described above, there is a serious problem of attention deficit, causing students to lose interest in receiving classes from their teachers, and it is necessary the Correction of this problem so that it does not become chronic in the future, through the application of strategies that promote an interesting education for students Therefore, this research yielded key conclusions, the first being that at least half of the students surveyed have attention deficit problems, grade 1, that is, it is not that strong, but since classes are taught and there is no news, some lose interest. by losing concentration and losing valuable study time, and the second that lack of attention can be generated by external elements, if the student is extremely distracted, he will lose concentration due to the minimum auditory or visual stimulus while in virtual classes, these stimuli range from advertisements on the internet, television.